Pengaruh Kualitas Pelayanan, Harga Tiket, Fasilitas dan Citra Destinasi terhadap Keputusan Berkunjung pada Kolam Renang Pandanaran Hills - Ananda, Fariz; Safitriani, Ayu; Firdaus; Astono, Ari Dwi; Septiana, Zulfa; Puspitasari, Irma (Business Perspective Journal, 2024)
The purpose of this research is to determine the influence of service quality, ticket prices, facilities, and destination image on the decision to visit the Pandanaran Hills swimming pool. The population in this study is unknown or cannot be determined, while the sample is 100 respondents. The method used in this research is a quantitative method involving visitors to the Pandanaran Hills Swimming Pool. The data collection technique in this research is nonprobability sampling with the accidental sampling method. The data analysis technique used in this research is Ordinal Logistic Regression using SPSS software. The research results show that based on the results of the w test, service quality has a positive and significant effect on visiting decisions with value and with significant value. Ticket prices have a positive and significant effect on visiting decisions. Facilities have a positive and significant influence on the decision to visit. Destination image has a positive and significant influence on the decision to visit. Simultaneously, Service Quality, Ticket Prices, Facilities and Destination Image have a positive and significant influence on the decision to visit visitors to the Pandanaran Hills Swimming Pool. Keywords: service quality, ticket prices, facilities, destination image, visiting decision